Developing a Web-Based Learning (E-Learning) in General Biology Subjects with Joomla Program - Seribulan, Muhamad Nurdin Matondang; Rahayu, Sri; Isfaeni, Hanum (Biosfer: Jurnal Pendidikan Biologi, 2014)
Web-based learning has been widely used as learning resources. Developing these learning resources is believed to provide beneficial for students. Therefore, this research was aimed to develop a web-based learning source for General Biology Course. It was developed by Joomla software version 1.5.6. This program was run and supported by Xampp version 1.6.1. in which Apache 2.2.4.. MySQL 5.0.37., and PHP version 5.2.1. were also included to offline program running support. The research was conducted on September – November 2012 in General Biology Course, Biology Department, Faculty of Mathematics and Science, State University of Jakarta. Material contents developed in this web were limited to animal structure. Samples were consisted of students, media expert, and learning material expert. Data were obtained through questionnaires. According to students, the material classified as very good (82.5%), whether 5 five other components including content (79.48%), visual design (70.33%), structure and navigation (76.94%), and interaction (78.67%) were categorized as good. Based on media expert assessment, the web content was classified as very good (81.25%), while the other components including web material (75%), visual design (70%), structure and navigation (70.83%), and also interaction (80%) were categorized as good. Lastly, this product was assessed by the learning material expert who categorized good for the following components: web material (75%), content (78.13), visual design (75%), structure and navigation (79.19%). The only component which got fair score was interaction (50%). Although most of the components were classified as good, some aspects of this web must be repaired.